Determination of M. quadriceps femoris of Various Athletes by an Ultrasonic Method - SATOU, Hironori; AKAIKE, Hidekazu (Japanese Journal of Sport Education Studies, 1988)
The purpose of this study was to clarify the morphological feature of the anterior thigh in various types of athletes by an ultrasonic method, and to investigate the relationship between the character of each given sport and the morphology of the players of the given sport by the ultrasonic method. The subjects, all male, used in this study were: 27 male volleyball players, 56 rugbyfootball players, 52 soccer players and 19 individuals not involved in a specific sport at the time of the study. Cross-sectional images of anterior thigh were taken by means of an ultrasonic apparatus (NEC SANEI Corp, TOMOACE 2H71). The results were as follows: (1) The total thickness of m. quadriceps femoris for rugbyfootball players was larger than in any other group. (2) The total thickness of m. quadriccps femoris for volleyball players and soccer players was nearly equal, whereas the m. rectus femoris of soccer players was thicker than that of the volleyball players. The m. vastus intermedius of volleyball players was thicker than that of the soccer players. (3) The depth of m. rectus femoris increased during contraction, but the m. vastus intermedius decreased. This was noted in all groups within this study.